Circulating tumor cells detected by reverse transcription-polymerase chain reaction for carcinoembryonic antigen mRNA: Distinguishing follicular thyroid carcinoma from adenoma - Sato, Takashi; Harao, Michiko; Nakano, Shogo; Jotsuka, Toko; Suda, Namiko; Yamashita, Jun-ichi (Surgery, 2005)
We prospectively tested whether circulating tumor cells could be detected in peripheral blood of patients with thyroid tumors by a reverse transcription-polymerase chain reaction (RT-PCR) to detect carcinoembryonic antigen (CEA) messenger RNA (mRNA). We assayed for CEA mRNA by RT-PCR in peripheral blood sampled before and 2 to 3 weeks after curative surgery for thyroid tumors in 121 patients. Blood samples from 7 patients with chronic thyroiditis and 7 healthy subjects served as controls. No control samples were positive for CEA mRNA by RT-PCR. Of 121 preoperative samples from patients with thyroid tumor, 6 were positive (5.0%). Preoperative frequencies of CEA mRNA positivity in benign tumor, papillary carcinoma, follicular variant papillary carcinoma, minimally invasive follicular carcinoma, and widely invasive follicular carcinoma were 0%, 0%, 0%, 44.4% (4/9), and 50.0% (2/4), respectively. Among positive patients only one, who had widely invasive follicular carcinoma, remained positive after surgery. RT-PCR detection of tumor cells in preoperative blood often can distinguish malignant from benign follicular thyroid tumors.